The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.msea.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue strain mapping via digital image correlation for Ni-based superalloys: The role of thermal activation on cube slip

Abstract: A deformation mechanism map for a Ni-based superalloy is presented during cyclic loading at low (300°C), intermediate (550°C), and high (700°C) temperatures for low (0.7%) and high (1.0%) applied strain amplitudes. Strain mapping is performed via digital image correlation (DIC) during interrupted fatigue experiments at elevated temperatures at 1, 10, 100 and 1000 cycles, for each specified loading and temperature condition. The DIC measurements are performed in a scanning electron microscope, which allows high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 41 publications
(52 reference statements)
3
36
0
Order By: Relevance
“…Each SEM was subjected to a single fatigue loading cycle via crystal plasticity to capture the micro-mechanical fields relative to each of microstructure. Based on prior digital image correlation of this material [68], it was observed that the slip bands form during the first loading cycle (and the number of slip bands were constant with respect to number of cycles for this particular loading). One cycle of the crystal plasticity simulation is sufficient to determine the heterogeneities in the stress distributions relative to the microstructural features [40], and the resulting micromechanical fields after one loading cycle are used for fatigue modeling purposes.…”
Section: Fatigue Simulationsmentioning
confidence: 99%
“…Each SEM was subjected to a single fatigue loading cycle via crystal plasticity to capture the micro-mechanical fields relative to each of microstructure. Based on prior digital image correlation of this material [68], it was observed that the slip bands form during the first loading cycle (and the number of slip bands were constant with respect to number of cycles for this particular loading). One cycle of the crystal plasticity simulation is sufficient to determine the heterogeneities in the stress distributions relative to the microstructural features [40], and the resulting micromechanical fields after one loading cycle are used for fatigue modeling purposes.…”
Section: Fatigue Simulationsmentioning
confidence: 99%
“…Advanced characterization techniques have emerged in the last decades, enabling the tracking of the deformation fields at the grain scale with applied loading by simultaneously combining digital image correlation (DIC) and Electron Backscatter Diffraction (EBSD) analysis [28]. Few investigations were performed at the scale of the grains for AM materials.…”
Section: Introductionmentioning
confidence: 99%
“…Digital image correlation (DIC) is an optical method which can quantify the deformation field on the specimen surface with the advantages of providing full-field, real-time, and non-contact measurements, as well as flexibility [27,28,29,30]. The method has been successfully applied to observe damage and failure in metallic materials during fatigue tests [31,32]. Short cracks during intergranular stress-corrosion cracking of austenitic stainless steel were detected by DIC [33].…”
Section: Introductionmentioning
confidence: 99%